STUDY OF THE EFFECT OF DOSE OF THE MOBILUX-LITE CONCENTRATE ON THE EFFICIENCY OF FERMENTATION OF SKIM MILK MOLOCHNOKISLYKH MICROORGANISMS - Alexey Lodygin; Maria Shatravina; Vladislav Ponomarev; Gennadiy Slusarev (Вестник Северо-Кавказского федерального университета)
Prospective directions of fermented dairy products technology improvement are reviewed. The relevance offermented dairy products enriched with food concentrate «MOBILUX» technology development is substantiated. The influence of the concentrate on skim milkfermentation efficiency by starter cultures Acidolact, Symbilact, Yoghurt is studied. The dynamics of titratable acidity and pH changing during the fermentation of control and experimental samples is shown.